Process optimization for foam-mat drying and physicochemical properties of leafy vegetable powder - Phongthai, Dr.Suphat (Food and Applied Bioscience Journal, 2023)
High quantities of vegetable waste are produced worldwide during primary production, so foam-mat drying was used to add value and create products from three leafy vegetables. Response surface methodology was applied to optimize the foaming parameters. The optimal condition was 3.44% egg albumen as a foaming agent, 5.78 g/mL vegetable: water ratio, and 17 min of whipping time, providing response values of 95.55% foam stability, 294.70% overrun, and a foam density of 0.21 g/mL. The major factor that significantly influenced these responses was egg albumen concentration (X1), whereas the quadratic terms of egg albumen and vegetable-water ratio (X12 and X22) mainly affected the foam density and overrun (P<0.05). The interaction between egg albumen concentration and vegetable: water ratio (X1X2) was a critical factor that affected foam stability. Optimal drying of vegetable foam at 50°C for 1.5 h provided comparable retention to freeze-drying for vitamin C (40%) in the vegetables. The derived vegetable powder had a relatively low moisture content (1.89–6.03%) and water activity (0.26–0.34). Egg albumen and drying conditions negatively impacted on the water solubility index and water absorption index. The derived powder showed promising oil (2.55 g/g) and glucose (50–68%) absorption capacities.